Rhetorical relations in university students’ presentations - Ducasse, Ana Maria; Brown, Annie (Journal of English for academic purposes, 2023)
The integration into the tertiary curriculum of problem-based learning, and the growing awareness of the need for university graduates to enter the workforce with highly developed communication skills, has led to a greater focus in academic classrooms on oral communication. One aspect of this is the increased use of monologic student oral presentation tasks, a requirement that presents challenges for international and local students alike. There is little research beyond lexical features that centres on the rhetorical level in student presentations. This study attempts to characterise the rhetorical moves within undergraduate oral presentations. The data comprise transcribed presentations by local and international high-scoring students in core first-year undergraduate subjects in three different faculties (n = 30). The methodology for the analysis was Rhetorical Structure Theory (RST). The analysis, which distributed RST relations into those contributing to the presentation's coherence and listener-oriented comprehensibility, identified the range and frequency of rhetorical moves within the dataset. Differences across disciplines appeared to be due to task requirements rather than disciplinary requirements per se. To conclude, we discuss the value of RST in the analysis of oral student data and its potential to inform the preparation of students for formal academic spoken discourse.